2019
DOI: 10.1021/acs.analchem.9b02497
|View full text |Cite
|
Sign up to set email alerts
|

Compound-Specific Chlorine Isotope Analysis of the Herbicides Atrazine, Acetochlor, and Metolachlor

Abstract: A gas chromatography-single quadrupole mass spectrometry method was developed and validated for compoundspecific chlorine isotope analysis (Cl-CSIA) of three chlorinated herbicides, atrazine, acetochlor and metolachlor, which are widespread contaminants in the environment. For each compound, the two most abundant ions containing chlorine (202/200 for atrazine, 225/223 for acetochlor and 240/238 for metolachlor) and a dwell time of 30 ms were determined as optimized MS parameters. A Limit of Precise Isotope Ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 43 publications
2
30
0
Order By: Relevance
“…Finally, recent developments on Cl-CSIA offer promising insights to investigate pesticide degradation pathways in surface waters using multi-element CSIA. 57,58…”
Section: Discussionmentioning
confidence: 99%
“…Finally, recent developments on Cl-CSIA offer promising insights to investigate pesticide degradation pathways in surface waters using multi-element CSIA. 57,58…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it would be particularly useful for contaminant accumulation, 125 source detection, 126 and the development of regulatory and monitoring strategies. 127 As additional elements, such as 2 H, 37,128 37 Cl, 129 and 34 S, 130 are included in the isotopic analysis of atrazine and its metabolite desethylatrazine in a given transformation process, the opportunity to assess the underlying reaction mechanism(s) increases. 131 This is particularly important for the phototransformation processes of agrochemicals, where different functional groups or bonds of a molecule might be involved.…”
Section: Future Outlook and Challengesmentioning
confidence: 99%
“…In addition, the synthesis of the working standards for acetochlor (Aceto1 and Aceto2) and S-metolachlor (Metola1 and Metola2) showed that organic synthesis can generate substance-specific isotope working standards also of more complex chlorinated organic compounds. These working standards become even more important as GC-qMS methods for stable chlorine isotope analysis of acetochlor and Smetolachlor were recently developed by Ponsin et al 45 However, two of the working standards show a chlorine isotope value larger than 0 ‰ (δ 37 Cl Aceto2 = 18.54 ± 0.20 ‰ and δ 37 Cl Metola2 = 5.12 ± 0.27 ‰). Therefore, future work has to strive for synthesis routes to generate AgCl in-house standards with a more positive chlorine isotope value that would optimize the characterization process of secondary inhouse working standards even further.…”
Section: ■ Conclusionmentioning
confidence: 99%